Faktor Yang Mempengaruhi Kepatuhan Pasien Hipertensi Rawat Jalan Peserta Askes Dan Dampaknya Pada Biaya - Barbara Azalya Sarifudin; Tri Murti Andayani; Achmad Fudholi (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Hypertension is a degenerative disease which is a health problem for all people. Treatment therapy in hypertensive patients takes a long time and regular control causes the tendency of patients to be disobedient during treatment so that the cost of treatment is expensive. The aim of the study was to find out the description of the therapy of hypertensive patients, the description of the compliance of hypertensive patients, the average cost of treatment, and the relationship between compliance and characteristics of costs. This type of research was observational with a retrospective cohort study design. The subjects of the study were hypertensive patients outpatient of Askes participants in Pandan Arang Hospital, Boyolali in 2011-2013. Data were analyzed descriptively including patient characteristics, description of treatment therapy, description of patient compliance, and the average cost of treatment. Chi-Square Test to determine the factors that influence compliance and correlation tests to analyze the relationship between patient adherence to treatment costs. The results showed that there were 310 patients suffering from stage 2 hypertension, the most widely used treatment was 41.81% hydrochlorothiazide + captopril. The number of patients who obeyed as many as 154 patients while patients who did not comply were 156 patients. The average treatment cost of patients who complied with was Rp. 2,202,435, and patients who were non-compliant were Rp. 2,831,860. There was no significant relationship between adherence to treatment costs for outpatients of Askes participants in Pandan Arang Hospital Boyolali.